The symbolic meaning of Lulo dance: Tolaki tribe culture as communication medium - Mega Alma Narwasty; Pamerdi Giri Wiloso; Gatot Sasongko (Masyarakat, Kebudayaan dan Politik, 2021)
Indonesia consists of various ethnic groups; the traditions and culture of each are different and have meaning. One of them is the Lulo dance from Southeast Sulawesi, which provides meaning and benefits to its supporters. This study aims to describe the Lulo dance movements’ meaning in the culture of the Tolaki tribe and its use as a traditional communication medium in maintaining harmonious and peaceful relations amid Indonesian society’s situations with so many different. This research used qualitative methods with descriptive analysis. The symbols of dance movements are analyzed with Barthes’s semiotic theory through two stages of signification to get Lulo dance’s meaning. Based on this study’s results, the symbolic messages conveyed in this dance have a meaning that identifies unity, harmony, and mutual respect for differences. The message is packed with movements displayed in dance performance: the hands hold each other, the movements of the hands and feet, and the formation in a circle. Lulo dance, which is also called social dance, can be followed by everyone without exception. Therefore, this dance can strengthen the relationships between every human being. The Lulo dance performance is one of Southeast Sulawesi traditions used to achieve a harmonious and peaceful social life.